Key Drivers of Sustainable Development in the Clay Roof Tile Industry of Sleman Regency - Nurcahyo, Eko; Yuliadi, Imamudin; Ma’ruf, Ahmad (Journal of Economics Research and Social Sciences, 2026)
The clay roof tile industry, a key subsector of small and medium enterprises (SMEs) in Sleman Regency, Indonesia, plays an important role in local economic development and employment. Despite its strategic significance, the industry has experienced declining productivity and a reduction in the number of business actors due to limited access to capital and technology, weak market competitiveness, and environmental degradation from raw material extraction. This study applies a systemic analytical approach using the MICMAC (Matrix of Cross-Impact Multiplication Applied to Classification) method to identify and examine direct and indirect interrelationships among 25 strategic variables across economic, technological, social, environmental, and institutional dimensions. The results reveal that environmental quality, capital constraints, and digital technology serve as primary upstream structural drivers shaping industrial sustainability. At the same time, institutional cohesion—particularly cooperatives and inter-actor relationships—acts as long-term systemic enablers. These drivers influence production efficiency, competitiveness, and environmental outcomes through complex interdependent pathways. The findings provide policy-relevant evidence for designing integrated development strategies that strengthen competitiveness, enhance resilience, and support sustainable industrial transformation. This study contributes to the literature on industrial cluster sustainability by demonstrating the value of a systems-based perspective for understanding structurally mediated sustainability dynamics in traditional manufacturing sectors.